Disclosure Within HIV-Affected Families - Grace Gachanja; Gary J. Burkholder; Aimee Ferraro (Frontiers Media SA, 2021)
While HIV/AIDS is a global public heath challenge, its impact is arguably greatest in the Sub-Saharan Africa (SSA), where new infections account for approximately 66% of the total number of HIV-positive persons globally. In SSA, medical, social, and economic resources are limited, thus necessitating innovative approaches to disease prevention. One of the mechanisms of prevention that is most promising occurs through HIV disclosure to family members (e.g., adult sexual partners) generally, and to children in particular. Our emphasis in this eBook is on HIV disclosure to children because it has multiple benefits, including improved adherence to antiretroviral medication treatment and understanding at an early age of the impact of sexual activity on the spread of HIV. While there is a noticeable gap in research on HIV disclosure to younger children, some of the general reasons for non-disclosure include concerns about fear of adult partners leaving relationships, and that children are too young to comprehend the severity of the situation and may tell others outside the family. Thus, it is critical to better understand how the HIV disclosure process happens (or does not happen) within HIV-affected families, as well as the best practices on how to disclose. In this eBook, we present a combination of empirical research studies and critical literature reviews that investigate the reasons for and for not disclosing HIV status within HIV-affected families and provide evidence-based practices that could be adopted by healthcare professionals to help HIV-positive parents facilitate disclosure activities within these families. This information can also be used by researchers, practitioners, and stakeholders who are in a position to influence policies on effective HIV disclosure practices, guidelines, and programs.